Congenital Sternal Cleft along with Persistent Left-Sided Superior Vena Cava: A Rare Presentation. (13th June 2013) - Saha, Anindya Kumar; Sardar, Syamal Kumar; Sur, Amitava
Abstract : Congenital sternal cleft is a rare abnormality resulting from fusion failure of sternum. It occurs in isolation or along with defects of abdominal wall, diaphragm, pericardium, and heart. Early surgical correction is required to protect the underlying structures for risk of cardiac compression. Here we report a case of 20-day female child presenting with congenital sternal cleft associated with multiple congenital heart disease and left-sided superior vena cava. She was operated by the cardiothoracic surgical team successfully and is doing well on followup. We discuss this rare case, imaging studies, and surgical strategy.